Conscientiousness and Altruism Impacting Supersonic Aircraft Fighter Pilots Performance (European Journal of Behavioral Sciences, 2020)
Research demonstrated that personality traits of fighter pilots have impact on their performance. The prediction of supersonic fighter pilots performance and professional success can be made by assessment of the levels of personality traits of those individuals that are selected to practice this profession.The present research examined if the personality traits (self-efficacy, orderliness, dutifulness and altruism) can predict the level of performance of the fighter pilots on supersonic aircraft, by using the “IPIP NEO” (International Personality Item Pool NEO) based on Big Five model and inter-evaluation method within group of supersonic fighter pilots. The results indicated that the high performance of supersonic aircraft fighter pilots can be predicted by high levels of above-mentioned personality traits and that there is a significant positive relation between those variables. The great need for success, the desire to adapt, to overcome their limitations and to face the difficulties, allow pilots to exercise their profession with all the special requirements of missions and the challenges in air combat.